Pyrimido[4, 5-g]quinazoline-4, 9-dione as a new building block for constructing polymer semiconductors with high sensitivity to acids and hole transport performance in organic thin film transistors. Issue 45 (2nd November 2015) - Quinn, Jesse; Guo, Chang; Sun, Bin; Chan, Adrian; He, Yinghui; Jin, Edward; Li, Yuning
Abstract : Polymers based on pyrimido[4, 5- g ]quinazoline-4, 9-dione (PQ) building block are sensitive to acids and show good hole transport performance in thin film transistors. Abstract : Pyrimido[4, 5- g ]quinazoline-4, 9-dione (PQ) was used for the first time as a building block for π-conjugated polymer semiconductors. Copolymers of PQ and bithiophene showed dramatic bathochromic shifts in their absorption spectra in the presence of protonic (acetic acid and trifluoroacetic acid) and Lewis (BBr3 ) acids, resulting from the strong interaction of the basic 1, 6-nitrogen atoms in the PQ unit with the acid. These polymers exhibited characteristic p-type semiconductor performance with hole mobilities of up to 6.4 × 10 −3 cm 2 V −1 s −1 in organic thin-film transistors (OTFTs). The potential bioactivity, high sensitivity to acids, and good field effect transistor performance of these PQ-based polymers will enable their application for bio- and chemo-sensors.